A comparison of the time course of action and laryngeal mask airway insertion conditions with different doses of mivacurium for day-case urologic surgery in children: a prospective cohort study - Hong Ye; Chunmiao Nian; Lijun Zhou; Yuman Xie; Fan Li; Tao Xue; Xueping Han (Frontiers in Pediatrics, 2024)
ObjectiveTo investigate the time course of action of different doses of mivacurium and determine the appropriate dose for laryngeal mask airway (LMA) insertion for day-case urologic surgery in children.MethodsA total of 105 patients who enrolled in this study between March 2021 and December 2021 were randomised into 3 groups: Group A (mivacurium 0.15 mg/kg, n = 35), Group B (mivacurium 0.20 mg/kg, n = 35) and Group C (mivacurium 0.25 mg/kg, n = 35). The different doses of mivacurium were injected before LMA insertion. The primary outcomes included the grading of conditions for the LMA insertion-18 score, onset time, recovery index and the duration that mivacurium was effective. Secondary outcomes included pulse oxygen saturation, mean blood pressure, heart rate and the incidence of adverse events.ResultsThe score of the conditions for LMA insertion in Group A was significantly lower than in Groups C and B (p < 0.005). There was a significant difference in the onset time between Groups B and A (p < 0.005). There was no significant difference in the overall incidence of adverse reactions between these groups (p > 0.05).ConclusionAnaesthesia with 0.2 mg/kg of mivacurium can effectively shorten the onset time and facilitate insertion of the LMA in children undergoing day-case urologic surgery.